The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00268-004-7541-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Surgery Using the Ligasure Vessel Sealing System

Abstract: Blood loss, a well-known risk factor for morbidity and mortality during liver resection, occurs during parenchymal transection, so many approaches and devices have been developed to limit bleeding. Surgical technique is an important factor in preventing intraoperative and postoperative complications. The aim of the present study was to determine whether the bipolar vessel sealing device allows a safe and careful liver transection, achieving a satisfactory hemostasis thus reducing blood loss and related complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 32 publications
3
81
0
Order By: Relevance
“…Interestingly, these advantages are almost exclusively achieved by using it as a dissecting tool to take down the intestinal mesentery, even though the presence of collagen in many other tissues renders this technology potentially suitable for numerous other applications. Experience in other organs is currently limited to a few clinical and experimental studies that have investigated the possibility of sealing and transecting collagen-containing tissues, such as the cystic duct [12], ureter [4], lung parenchyma [11,14], liver [7,10], hemorrhoids [1,9], and appendix [20]. The present study differs fundamentally from these studies since the LigaSure was not applied for its dissecting properties but for its possible reconstructive capacities, the creation of intestinal anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these advantages are almost exclusively achieved by using it as a dissecting tool to take down the intestinal mesentery, even though the presence of collagen in many other tissues renders this technology potentially suitable for numerous other applications. Experience in other organs is currently limited to a few clinical and experimental studies that have investigated the possibility of sealing and transecting collagen-containing tissues, such as the cystic duct [12], ureter [4], lung parenchyma [11,14], liver [7,10], hemorrhoids [1,9], and appendix [20]. The present study differs fundamentally from these studies since the LigaSure was not applied for its dissecting properties but for its possible reconstructive capacities, the creation of intestinal anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the use of Ligasure System is not correlated with an increase of the rate of postoperative bile leaks and in some study bile leakage was nihill [76]- [127] and that proves his effectiveness in obliterate also bile vessel. D: after the application the coagulated tissue often sticks to the instrument's jaws causing new bleeding when the device is moved away; BVSD seems to be less effective in presence of cirrhosis for two reasons: first the portal hypertension correlated with cirrhosis causes thinning of the dilate portal vein's walls and makes their obliteration less effective; second cirrhosis makes crushing technique difficult and the hepatic tissue between the blades may disperse the power applied causing vessel to bleed [128]; moreover it seems to be ineffective in cystopericystectomy [77] (even if some surgeons sustain his effectiveness in this surgery [78]). Ligasure vessels sealing system has been widely use during liver transection in a "blind" way [70]- [71], achieving parenchymal fracture and vessel sealing in the same time without identìfication of tiny vasculatures and bile ducts.…”
Section: Dmentioning
confidence: 99%
“…BVSD is capable to obliterate the lumen of veins and arteries up to 7 mm in diameter by the fusion of elastin and collagen proteins of the vessel walls; that makes BVSB the only safe and real alternative to sutures and clips for sealing vessel [68], [69], [70]. A: BVSD coagulates sealing vessels up to 7 mm in diameter with minimal charring, thermal spread or smoke, it's capable to reduce blood loss and the need for vessel occlusion techniques if compared to traditional techniques [8], [71], [72], A recently published randomized controlled trial demonstrated that the use of Ligasure in combination with a clamp crushing technique resulted in lower blood loss and faster transaction speed in minor liver resections compared with the conventional technique of electric cautery or ligature for controlling vessels in the transection plane [73]. Otherwise a more recent randomized trial from the same team was not able to show a real difference between the traditional techniques and the Ligasure vessel sealing system [74].…”
Section: Dmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been employed for liver transection with proven effectiveness 54,55 . The liver tissue can be crushed between the blades of the device and then coagulation energy is applied to seal the vessels.…”
Section: Successful Hepatectomy Techniques Of Parenchymal Transectionmentioning
confidence: 99%